Phytochemical evaluation and in-vitro anti-bacterial and antioxidant effect of extract of Solanum xanthocarpum and Achyranthes aspera - Kanchan Mathur; Reena Gupta (Journal of Applied Pharmaceutical Research, 2026)
Background: This study investigates the phytochemical composition, antioxidant activity, and antibacterial properties of extracts from Solanum xanthocarpum and Achyranthes aspera. Achyranthes aspera exhibited 65.864 % inhibition with an IC50 value of 31.056 µg/mL, and Solanum xanthocarpum showed 55.385% inhibition with an IC50 value of 51.920 µg/mL. Methodology: The total phenolic content (TPC) and total flavonoid content (TFC) were measured using the Folin-Ciocalteu assay and aluminum chloride colorimetric method, respectively. Antioxidant activities were evaluated using DPPH radical-scavenging and reducing power assays. The antibacterial activity against Streptococcus mutans was determined using the well diffusion method. Result and Discussion: The TPC of Solanum xanthocarpum and Achyranthes aspera extracts were 77.80 mg  GAE/g and 98.40 mg GAE/g, respectively, while the TFC were 82.66 mg RE/g and 136.66 mg RE/g. In the DPPH assay, Achyranthes aspera exhibited 65.864 % inhibition with an IC50 value of 31.056 µg/ml, and Solanum xanthocarpum showed 55.385% inhibition with an IC50 value of 51.920 µg/mL. The reducing power assay indicated significant antioxidant potential, especially for Achyranthes aspera. The antibacterial activity against Streptococcus mutans MTCC 389 revealed that Achyranthes aspera exhibited a maximum inhibition zone of 23±1.732 mm. At the same time, Solanum xanthocarpum showed a maximum inhibition zone of 20±1 mm at a concentration of 2 mg/mL. Conclusion: The extracts of Solanum xanthocarpum and Achyranthes aspera demonstrate significant antioxidant and antibacterial activities, highlighting their potential as natural sources of antimicrobial and antioxidant agents. Further research is needed to isolate bioactive components, elucidate their mechanisms of action, and assess their potential cytotoxic effects on human cells.